New private media in French-speaking West African Countries: Problems and Prospects - Frère, Marie-Soleil (Afrika Focus, 1996)
In this paper, we will try to take a closer look at the rise of the democratic transition in two French-speaking West African countries: Benin, often referred to as "the country where it all started", and Niger that can be considered as one of the weak copies of the Beninese model. In the first part of the paper, we will try to show how the democratic experiment took place in both countries and how private and government-owned media came to play an active role in all main political changes. In the second part, we will take a closer look at the role of the new private written press in the democratic transition and try to mention the main problems facing both the press and the democracy implementation. Eventually, we will mention the recent political events that occurred in Benin and Niger, showing that the democratic process has generated very different outcomes. KEYWORDS: Africa, Benin, Niger, democracy, press, mass-media, democratic transition